Penyelesaian Wanprestasi Perjanjian Lelang Mobil (Studi Kasus Di Japan Bike Auction Cabang Sidoarjo) (Jurnal Begawan Hukum (JBH), 2024)
This research aims to examine legal protection and the consequences of default from buying and selling auctions via Instagram media. The type of research used is empirical juridical law, legal research carried out by collecting primary data or data obtained directly from research subjects through direct interviews. Based on the results of research at PT Japan Bike Auction regarding the settlement of auction agreement defaults, the following conclusions can be drawn: 1) Default at PT Japan Bike Auction Sidoarjo branch occurred due to several factors that triggered disagreements over the payment of proceeds after the car auction. These factors are divided into two, namely internal factors and external factors. The internal factors in this research are the element of intention, such as the lack of good faith on the part of the bidder in repayment of payments and the lack of legal awareness in the local community. The external factors in this research are due to inaccuracies between the physical vehicle and the vehicle documents that have been issued by the authorities and mistakes in making random bids and not being considered first when conducting a car auction at PT Japan Bike Auction Sidoarjo Branch. 2) The results of this research Indeed, it is not entirely in accordance with the articles stated in the Civil Code. However, the problem of default above can be resolved by means of family deliberation mediation so that this problem of default does not lead to court, because in resolving this problem the auction body and the bidders have discussed it. carefully so that this problem can be resolved quickly and does not drag on and this problem does not interfere with other auction processes that will be carried out by PT Japan Auction.